2013
DOI: 10.1016/j.tetlet.2013.06.041
|View full text |Cite
|
Sign up to set email alerts
|

Direct conversion of glycerol into formic acid via water stable Pd(II) catalyzed oxidative carbon–carbon bond cleavage

Abstract: Using our tridentate NHC-amidate-alkoxide Pd(II) complex, we developed a catalytic method for oxidative C-C bond cleavage of glycerol. The glycerol was degraded exclusively to formic acid and CO2. Two possible degradation pathways were proposed through 13C labeled studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 42 publications
1
19
0
Order By: Relevance
“…Alcohol functionalities appear to be essential to direct the selective C–C bond cleavage, but binding of the aryl ring to the vanadium center as a phenolate shuts down the catalytic activity. To probe whether unactivated alcohols can undergo this remarkable photocatalyzed C–C cleavage, both glycerol (a by-product of biodiesel production) 40 and 1-butanol were used as substrates. Gratifyingly, formic acid was observed as one of the products for both substrates as anticipated ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Alcohol functionalities appear to be essential to direct the selective C–C bond cleavage, but binding of the aryl ring to the vanadium center as a phenolate shuts down the catalytic activity. To probe whether unactivated alcohols can undergo this remarkable photocatalyzed C–C cleavage, both glycerol (a by-product of biodiesel production) 40 and 1-butanol were used as substrates. Gratifyingly, formic acid was observed as one of the products for both substrates as anticipated ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Lastly, only trace amounts of oxalic acid were detected by 13 C NMR under our standard conditions after four hours, corroborating that this route was minor and the α-oxidation pathway would be predominant. As suggested in our previous work, 11 catalyst 1 acts as a bidentate system, simultaneously activating an aldehyde and alcohol in close proximity of each other, forming a five-membered heterocycle glucose adduct. This enhances the nucleophilic attack of peroxide, promoting the α-oxidation in a systematic sequential order.…”
mentioning
confidence: 82%
“…On the other hand, glyceraldehyde, dihydroxyacetone, glyoxylic acid, mesoxalic acid, and oxalic acid (Nguyen et al, 2020) were not detected under the experimental condition in this study. These results indicated that the partial oxidation of GA to TA (Mimura et al, 2014a), and the oxidative degradation of glycerol to form GCA and FA (Pullanikat et al, 2013; Xu et al, 2014) had occurred, with the dehydration/rearrangement of glycerol to generate LA (Shen et al, 2010) also occurring. By increasing the molar ratio to 4, the glycerol conversion increased to about 64%, but the selectivity of the other products did not change.…”
Section: Methodsmentioning
confidence: 98%